2019
DOI: 10.1073/pnas.1818430116
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of test–retest reliabilities of self-regulation measures

Abstract: The ability to regulate behavior in service of long-term goals is a widely studied psychological construct known as self-regulation. This wide interest is in part due to the putative relations between self-regulation and a range of real-world behaviors. Selfregulation is generally viewed as a trait, and individual differences are quantified using a diverse set of measures, including selfreport surveys and behavioral tasks. Accurate characterization of individual differences requires measurement reliability, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
312
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(384 citation statements)
references
References 54 publications
12
312
9
Order By: Relevance
“…Of note, such concerns about the construct validity of behavioral measures are by no means limited to aggression tasks. Meta‐analytic reviews observe null‐to‐small relations between self‐report and task measures of impulsivity (e.g., Cyders & Coskunpinar, 2011), and recent evidence suggests poor psychometric properties of many functional neuroimaging tasks (Elliott et al, 2019) and behavioral measures of self‐regulation (Enkavi et al, 2019). This criticism, of course, does not excuse or nullify critiques of the CRTT, but it is important to note that the difficulty of integrating self‐report and behavioral measures is a field‐wide dilemma and that the current study found more consistent relations between self‐reported traits and putatively relevant tasks than have been found when using many other laboratory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, such concerns about the construct validity of behavioral measures are by no means limited to aggression tasks. Meta‐analytic reviews observe null‐to‐small relations between self‐report and task measures of impulsivity (e.g., Cyders & Coskunpinar, 2011), and recent evidence suggests poor psychometric properties of many functional neuroimaging tasks (Elliott et al, 2019) and behavioral measures of self‐regulation (Enkavi et al, 2019). This criticism, of course, does not excuse or nullify critiques of the CRTT, but it is important to note that the difficulty of integrating self‐report and behavioral measures is a field‐wide dilemma and that the current study found more consistent relations between self‐reported traits and putatively relevant tasks than have been found when using many other laboratory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we have shown the value of using beta bursts to reveal the fine timing of stopping related brain activity (see also Wessel, 2019). Taken together, these methods provide a good basis for testing whether the variation in sub-processes of action-stopping might better relate to real-world self-control and impulsivity than SSRT (Friedman and Miyake, 2004;Lijffijt et al, 2004;McLaughlin et al, 2016;Chowdhury et al, 2017;Enkavi et al, 2019;Skippen et al, 2019).…”
Section: Prolongation Of Canceltime Is Unrelated To Delayed Emg Onsetmentioning
confidence: 99%
“…We speculate that it may restrict what is being measured to financial risk-taking, and no longer generalize to other manifestations of impulsivity. In fact, a recent study on self-regulation, a related construct to delay discounting, suggests that behavioral measures have lower test-retest reliabilities than survey measures (Enkavi, Eisenberg, Bissett et al, 2019). This finding may reflect the fact that behavioural measures largely assess situation-specific behaviours while self-report measures largely assess traits.…”
Section: Discussionmentioning
confidence: 99%